Twinning behavior of orthorhombic-α" martensite in a Ti-7.5Mo alloy. Issue 1 (31st December 2019) - Ji, Xin; Gutierrez-Urrutia, Ivan; Emura, Satoshi; Liu, Tianwei; Hara, Toru; Min, Xiaohua; Ping, Dehai; Tsuchiya, Koichi
ABSTRACT: Deformation microstructure of orthorhombic-α" martensite in a Ti-7.5Mo (wt.%) alloy was investigated by tracking a local area of microstructure using scanning electron microscopy, electron back-scattered diffraction, and transmission electron microscopy. The as-quenched α" plates contain {111}α" -type I transformation twins generated to accommodate transformation strain from bcc-β to orthorhombic-α" martensite. Tensile deformation up to strain level of 5% induces {112}α" -type I deformation twins. The activation of {112}α" -type I deformation twinning mode is reported for the first time in α" martensite in β-Ti alloys. {112}α" -type I twinning mode was analyzed by the crystallographic twinning theory by Bilby and Crocker and the most possible mechanism of atomic displacements (shears and shuffles) controlling the newly reported {112}α" -type I twinning were proposed. Abstract : uf0001